AN ESTIMATION OP HEAT CHANGES IN THE BAY OF BENGAL OFF VISAKHAPATNAM - Ramasastry, A A (Indian Journal of Fisheries, 2016)
Heat changes in the upper layers of the sea result from a number of factorswhich might be conveniently divided into two groups. They are (1) theenergy transfer processes and (2) the advective processes. Over limitedareas and time intervals the heat budget of the oceans has been studied previouslyby a number of scientists and thus the factors that change the temperatureare fairly well known and are listed in detail by Severdrup etal.(1942) and LaFond (1954).